Factors Influencing Technology Adoption Among SMES: A Case Study of Youtap and The Role of Performance Expectancy and Effort Expectancy - Sengkalit, Dhanang; Chair, Ummil; Abdullah, Tengku Mohd Khairal (Syntax Literate, 2025)
This study examines the factors influencing technology acceptance among Indonesian Micro, Small, and Medium Enterprises (MSMEs) by analyzing Youtap, a Point of Sales (POS) service provider, as a case study. The research specifically investigates the roles of Performance Expectancy and Effort Expectancy in shaping the intention to adopt such services. Performance Expectancy refers to the perceived benefits and productivity enhancements offered by the technology, while Effort Expectancy relates to the ease of use and simplicity of the system. The study employs a quantitative approach, gathering data from MSME owners and operators through structured surveys. Statistical analysis reveals that both Performance Expectancy and Effort Expectancy significantly influence the intention to adopt Youtap. MSMEs recognize the potential of Youtap to streamline business operations, improve efficiency, and enhance customer engagement, while also valuing the platform's intuitive design and ease of integration. These findings contribute to the broader understanding of technology acceptance within the MSME sector in Indonesia, a critical driver of the national economy. The study highlights actionable insights for technology providers, emphasizing the need to align their solutions with the specific needs and expectations of MSMEs. Strategies that enhance perceived benefits and ease of use can improve adoption rates, fostering technological innovation and competitiveness in the sector.